Art Galleries, Academia, and Women in Fur Masks: A Case Study of Using Visual Art to Promote Engaged Classroom Learning - Brickner, Rachel K.; Dalton, Laurie (Atlantis)

(untitled) (Mount Saint Vincent University, 2012)
This article describes a collaboration between a Gender and Development professor and the Director of the Acadia University Art Gallery in designing an activist visual art project based on an exhibit of the Guerrilla Girls. We argue that faculty-gallery collaboration is a critical, but underused, component of teaching and learning on campuses.